Poleward increase in feeding efficiency of leafminer Stigmella lapponica (Lepidoptera: Nepticulidae) in a latitudinal gradient crossing a boreal forest zone - Kozlov Mikhail V; Zverev Vitali; Sandner Tobias M; van Nieukerken Erik J; Zvereva Elena L (WILEY, 2025)
Damage to plant communities imposed by insect herbivores generally decreases from low to high latitudes. This decrease is routinely attributed to declines in herbivore abundance and/or diversity, whereas latitudinal changes in per capita food consumption remain virtually unknown. Here, we tested the hypothesis that the lifetime food consumption by a herbivore individual decreases from low to high latitudes due to a temperature-driven decrease in metabolic expenses. From 2016 to 2019, we explored latitudinal changes in multiple characteristics of linear (gallery) mines made by larvae of the pygmy moth, Stigmella lapponica, in leaves of downy birch, Betula pubescens. The mined leaves were larger than intact leaves at the southern end of our latitudinal gradient (at 60 degrees N) but smaller than intact leaves at its northern end (at 69 degrees N), suggesting that female oviposition preference changes with latitude. No latitudinal changes were observed in larval size, mine length or area, and in per capita food consumption, but the larval feeding efficiency (quantified as the ratio between larval size and mine size) increased with latitude. Consequently, S. lapponica larvae consumed less foliar biomass at higher latitudes than at lower latitudes to reach the same size. Based on space-for-time substitution, we suggest that climate warming will increase metabolic expenses of insect herbivores with uncertain consequences for plant-herbivore interactions.